Sutan Sjahrir: Manusia dan Noktah Sejarahnya di Timur Tengah - Herdi Sahrasad (Budapest International Research and Critics University, 2018)
This treatise opens with a small question: Why Sutan Sjahrir married Poppy Saleh Mengundiningrat in Cairo, Egypt in the 1950s and did not in Jakarta? Poppy was studying at the London School, England and Sjahrir in Jakarta, the two then flew to Cairo and married there, witnessed by Soedjatmoko, a child of revolution, which is also a leading intelligentsia and political cadre of Sjahrir. Apparently, the First Prime Minister of the Republic of Indonesia, Sutan Sjahrir had a speck of history in the Middle East during the war of independence 1945-1949, which makes its way to Egypt to meet with the Arab leaders, fighters, intellectuals, activists and warriors. Sjahrir even met Hassan al-Bana, founder of the Muslim Brotherhood persistent against colonialism and imperialism in the Muslim world, especially the Middle East. Sjahrir asked the Arab world to mobilize supports for the independence of Indonesia. Sjahrir known as the Socialists that grow from the Minangkabau world and the Western-educated to find a foothold in the Middle East struggle to carry out a diplomatic mission of the President Soekarno and Vice President M. Hatta, for the people of Indonesia. We should remember and recall, Sjarir as a hero, eventhough he is almost forgotten by this nation.